Ferroptosis and Cancer Therapy Review - Sunday, James Agbu; Olawale, Otitujo; Umaru, Isaac John; Dauda, Maianguwa Abdulrsashid (Darul Yasin Al Sys, 2024)
Ferroptosis is a type of intracellular iron-dependent cell death that is different from autophagy, necrosis, and apoptosis. Ferroptosis is necessary for tumour suppression, according to a number of studies, which opens up new therapy options for cancer. The establishment of resistance to cancer therapy is one of the most significant ongoing challenges. The subject of conquering drug resistance has been the focus of numerous preclinical and clinical studies. Interestingly, ferroptosis has been associated with treatment resistance for cancer, and ferroptosis stimulation has been demonstrated to reverse drug resistance. The current knowledge of ferroptosis-inducing and ferroptosis defence mechanisms analyses the functions and mechanisms of ferroptosis in tumour immunity and tumour suppression, conceptualises the various ways that cancer cells are vulnerable to ferroptosis, and investigates therapeutic approaches for ferroptosis targeting in cancer. Cancer is one of the most terrible illnesses that can kill a person worldwide. There are several ways to treat cancer, including surgery, chemotherapy, and radiation. Analysis of the sensitivity of cancer cells to ferroptosis, which is impacted by their elevated reactive oxygen species levels and particular mutation profiles, opens up new possibilities for improving the efficacy of already used cancer treatments. This review included the state of knowledge about the induction and defence mechanisms of ferroptosis, the function and mechanisms of ferroptosis in tumor suppression, and treatment approaches for tumor-induced ferroptosis.